The Potential of Herbal Soap From Betel Leaves to Increase The Income of Non-Productive Communities in Lampulo Village, Banda Aceh: Potensi Sabun Herbal Dari Daun Sirih untuk Meningkatkan Pendapatan Masyarakat Non Produktif di Desa Lampulo, Banda Aceh - Meilina, Rulia; Andika, Fauziah; Dina Kali Kulla, Periskila (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The use of soap is one of the most effective ways to protect the skin from bacterial infections and prevent skin diseases. Soap, whether in solid or liquid form, functions to cleanse the skin of dirt, oil, and bacteria. Untreated bacterial infections can cause inflammation in tissues or organs, disrupt organ function, and weaken the immune system. This community service program aimed to enhance public knowledge about hygiene, health, and the potential benefits of betel leaves (Piper betle L.), while also improving the skills and creativity of housewives in processing natural ingredients into environmentally friendly herbal soap products. Additionally, the program sought to broaden participants’ understanding of entrepreneurship, including business planning, marketing, and product management. The program was conducted from July to October 2024, involving 15 non-working housewives in Lampulo Village. Activities included educational sessions and practical training on making betel leaf-based herbal soap. The results showed a significant improvement in participants’ knowledge and skills in utilizing natural ingredients to create value-added and eco-friendly herbal products. This program not only provided direct benefits in the form of useful products but also contributed to improving the community’s quality of life by empowering knowledge, practical skills, and raising awareness of health and environmental sustainability.